Rewards and sanctions to enhance stroke quality in tennis training - Weber, K.; Pieper, S.; Fust, C. (Medicine and Science in Tennis, 2006)
The goal of this study was to examine how the use of rewards and sanctions actually influences the performance behaviour of tennis players. Twelve 12 semi- and professional tennis players aged 17 to 27 years performed five different types of tests. In three of the tests, a sanction (kangaroo jump) or reward (milk shake) was added. In the various forms of tennis training, the threat of a sanction leads to a consistent slight increase in heart rate and subjective performance perception, without an increase of blood lactate. The prospect of a reward led to an increase in heart rate and subjective load perception, compared to 'normal' training.